A model of religiosity integration in sustainable tourism development (The case of Tenganan Pagringsingan Village, Bali, Indonesia) - I Ketut Budarma (Journal of Applied Sciences in Travel and Hospitality, 2024)
The research in Tenganan Pegringsingan village in Bali, Indonesia examines the relationship between religiosity, convention (awig-awig) environmental sustainability, and sustainable tourism development. The study explores how the village's cultural practices and social structures impact its ecological balance. The method used is descriptive qualitative to examine potential challenges faced by the village. The findings emphasize the importance of preserving traditional practices in maintaining the ecological health of the region. The village's commitment to cultural preservation and environmental sustainability is crucial for its sustainability and resilience. The research also identifies five challenges faced by the village, including tourism governance, friction between customs and tourism, preservation of local wisdom, economic life and cultural-based tourism, and informal education for endogamous marriages. To address these challenges, a comprehensive model is proposed that integrates religiosity, traditional conventions, tourism governance, local wisdom, informal education, cultural tourism-based economy, cultural friction, and integration. This model ensures that tourism development aligns with the village's religiosity and traditional practices, maintains cultural integrity, and promotes sustainable economic growth while preserving the community's way of life.